Secured Hardware Accelerators for DSP and Image Processing Applications - Sengupta, Anirban ca. 20./21. Jahrhundert (IET materials, circuits and devices series, 2020)
Written by an acknowledged expert in the field, this book focuses on approaches for designing secure hardware accelerators for digital signal processing and image processing. State-of-the art security and optimization algorithms are presented, and their roles in the design of secured hardware accelerators explored